The expression of path in three satellite-framed languages a cognitive study of Polish, Russian, and English - Łozińska, Joanna (2019)
Cross-linguistic studies of the lexicalization of motion tend to contrast satellite- with verb-framed languages (e.g. Slobin 1996; 2004; Cardini 2008; Özçalışkan & Slobin 2003; Kopecka 2004; Fargard et al. 2013, etc.) and concentrate less frequently on intra-typological analyses (but cf. e.g. Filipović 2007; Hasko 2010; Ibarretxe-Antuñano 2009; Ibarretxe-Antuñano & Hijazo-Gascón 2012). Even fewer studies contrast genetically related languages (but cf. e.g. Łozińska 2018). The main aim of this study was to establish the path-saliency cline of three satellite-framed languages: Polish, Russian, and English. The analysis was based on elicited data. The overall patterns of expressing the path of motion in the three languages were shown to be caused by their belonging to the same typological category. The differences could be attributed, to a large extent, to differences in the morphological structures and in the lexical repertoires of motion-coding expressions available to the speakers of the three languages. However, the analysis of descriptions of three specific spatial situations (i.e. vertical, boundary-crossing, and deictic relations) pointed to other factors that may influence path coding in the three languages. Thus, despite the satellite-verb character of the languages examined and the morpho-syntactic differences between them, all our participants, who were native speakers of the three languages examined, tended to code vertical relations by means of path verbs. The number of tokens of path verbs used to code this particular spatial relation was found to be higher than the number of tokens of path verbs used to code deictic or boundary-crossing motion.
Das Hauptziel dieser Studie ist die Ermittlung der Grammatikalisierung des Pfad-Hervorragens in drei Satellite-Framed Languages: Polnisch, Russisch und Englisch. Die Analyse basierte auf hervorgerufenen Daten. Es wurde gezeigt, dass die allgemeinen Muster für den Ausdruck des Pfads der Bewegung in den drei Sprachen durch ihre Zugehörigkeit zur selben typologischen Kategorie begründet werden. Die Unterschiede können den Unterschieden in den morphologischen Strukturen und den lexikalischen Repertois von Bewegungs-kodierenden Ausdrücken zugeordnet werden, die den Sprechern der drei Sprachen zur Verfügung stehen. Die Analyse der Beschreibungen von drei räumlichen Situationen (d. h. vertikale, grenzüberschreitende und deiktische Beziehungen) deutete jedoch auf andere Faktoren, die die Pfadkodierung in den drei Sprachen beeinflussen können. Somit tendierten – trotz des Satelliten-Verb-Charakters der drei untersuchten Sprachen und der morpho-syntaktischen Unterschiede zwischen ihnen – alle unsere Teilnehmer zur Kodierung vertikaler Beziehungen mithilfe von Pfadverben. Die Anzahl der Zeichen von Pfadverben, die zur Kodierung dieser speziellen räumlichen Beziehung verwendet wurde, erwies sich als höher als die Anzahl der Zeichen von Pfadverben, die zur Kodierung von deiktischen oder grenzüberschreitenden Bewegungen verwendet wurden.
Bibliografija: str. 57-60.
Summary ; Zusammenfassung.
Keywords: Glagoli kretanja -- Lingvističke studije -- Verbalni prefiks